2020
DOI: 10.2147/jhc.s277453
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of the Pretreatment Lung Immune Prognostic Index with Survival Outcomes in Advanced Hepatocellular Carcinoma Patients Treated with PD-1 Inhibitors</p>

Abstract: Purpose At present, there are no validated biomarkers that can predict whether patients with advanced hepatocellular carcinoma (aHCC) are likely to benefit from anti-PD-1 therapy. We aimed to determine whether lung immune prognostic index (LIPI) is associated with outcomes in patients with aHCC treated with PD-1 inhibitors. Patients and Methods Patients undergoing initial treatment with PD-1 inhibitors for aHCC at a single center from January 1, 2015 to August 31, 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…Therefore, it might be more appropriate if the cohort was separated into two groups (LIPI good and LIPI intermediate/poor). In a previous study on the association of pretreatment LIPI with survival time in advanced hepatocellular carcinoma patients, the population was also divided into two groups (LIPI good and LIPI intermediate/poor) (40). Our findings showed that pretreatment LIPI was associated with PFS and OS in SCLC patients with first-line ICI treatment in univariate analysis.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, it might be more appropriate if the cohort was separated into two groups (LIPI good and LIPI intermediate/poor). In a previous study on the association of pretreatment LIPI with survival time in advanced hepatocellular carcinoma patients, the population was also divided into two groups (LIPI good and LIPI intermediate/poor) (40). Our findings showed that pretreatment LIPI was associated with PFS and OS in SCLC patients with first-line ICI treatment in univariate analysis.…”
Section: Discussionsupporting
confidence: 50%
“…After reviewing the remaining 39 articles via the full-text view, 27 full-text articles were excluded due to lack of intended outcomes (OS, PFS), HR with 95% CI or repeatedly published studies. Finally, 12 studies published between 2018 and 2020 were included in this analysis (11)(12)(13)(14)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Retrieval Results and Study Characteristicsmentioning
confidence: 99%
“…It has been demonstrated as a prediction tool that differentiates likely prognosis of patients with NSCLC initiating ICI treatment [ 8 , 11 , 12 , 13 , 14 , 15 , 16 ]. Studies have also demonstrated that LIPI may differentiate prognosis in patients treated with ICIs in other cancer types, including breast cancer, hepatocellular carcinoma, melanoma, renal cell carcinoma, small cell lung cancer, and urothelial carcinoma [ 12 , 17 , 18 , 19 , 20 ]. In addition to behaving as a prognostic biomarker, LIPI has been proposed as a method to classify patients subgroups with disparities in ICI treatment efficacy (i.e., a predictive biomarker) [ 13 ], albeit findings have been conflicting [ 8 , 14 , 15 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%